ANALISIS RESISTANSI COIL KAWAT TEMBAGA TERHADAP PERUBAHAN SUHU SANGAT RENDAH SEBAGAI RANCANG DASAR PENGUKURAN SUHU RENDAH - Riswanto, Riswanto (Jurnal Pendidikan Fisika, 2015)
The resistance of a wire conductor depend of the wire material. Copper wire formed into a coil shape an effective form to produce a large resistance. Copper wire resistance influenced bytemperature about it. Coil of copper wire has a good response at low temperature changes produced by liquid nitrogen. This response is shown by the index value determination (R2 = 0.999) which is close to the value 1,that means changes in temperature approaching a linear response to changes in a voltage. The results can be used as a basis for the design of the low-temperature measurements cheaper